2009
DOI: 10.1093/europace/eup216
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy and clinical context in deceased patients with implanted pacemakers and defibrillators: intracardiac findings near their leads and electrodes

Abstract: We have found (i) thrombi on ventricular/atrial leads in 33/48%, (ii) bipolar lead rings fixed by fibrous tissue in 68/22%, (iii) connective tissue bridges or tunnels in ventricle/atrium in 87/71%, and (iv) ventricular leads fixed to valve or penetrating chordae in 46% of patients. We do recommend caution when extracting leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 17 publications
3
47
0
1
Order By: Relevance
“…18,19 However, these studies did not specifically include patients with endovascular pacemakers and defibrillators. The fact that endovascular leads are a nidus for thrombus development 6,9 and adopt an intracardiac course that frequently is in juxtaposition to the interatrial septum likely accounts for the strong association we observed between PFO and stroke/TIA in device recipients (Figure 3). This is the first systematic evaluation of the risk of systemic embolic events among patients with implanted endocardial pacemaker or defibrillator leads who have an incidentally identified PFO on echocardiography.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…18,19 However, these studies did not specifically include patients with endovascular pacemakers and defibrillators. The fact that endovascular leads are a nidus for thrombus development 6,9 and adopt an intracardiac course that frequently is in juxtaposition to the interatrial septum likely accounts for the strong association we observed between PFO and stroke/TIA in device recipients (Figure 3). This is the first systematic evaluation of the risk of systemic embolic events among patients with implanted endocardial pacemaker or defibrillator leads who have an incidentally identified PFO on echocardiography.…”
Section: Discussionmentioning
confidence: 85%
“…6 A study using intracardiac echocardiography at the time of a planned electrophysiological procedure found mobile thrombi attached to leads in 30% of patients. 9 These thrombi were rarely seen with the use of transthoracic echocardiography (TTE), reflecting their small size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…63 A study of autopsy findings of patients with CIEDs found other issues relating to leads such as thrombi on ventricular/atrial leads (48 %), bipolar lead rings fixed by fibrous tissue (22 %), connective tissue bridges or tunnels in ventricle/atrium (71 %) and ventricular leads fixed to valve or penetrating chordae (46 %). 64 Depending on their location, such connective tissue surrounding the leads, as well as leads partially positioned outside the vessels or the heart, may increase the risk of complications during lead extraction. The present HRS and EHRA recommendations do not fully cover the timing of reimplantion or the treatment of pacemaker and ICD dependent patients, partially due to lack of studies comparing strategies.…”
Section: Management Of Cardiac Implantable Electronic Device Infectionmentioning
confidence: 99%
“…Venous obstruction is caused mainly by the adhesions between the lead and the vascular wall. Their presence is a cause of the most severe difficulties related to lead extraction [10,14]. Adhesions are often found in the subclavian or/and innominate vein, particularly in young people.…”
Section: Konsekwencje Uszkodzenia Elektrody Przedstawionego Na Poprmentioning
confidence: 99%